Economics of sealing horizontal silos - Huck, G.L.; Turner, J.E.; Siefers, M.K.; Brent, B.E.; Bolsen, K.K.; Young, Matthew A.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Determining the value of silage saved by effectively sealing a horizontal silo requires only a few simple calculations, but it is still a concept that is often overlooked by many livestock producers who store large amounts of silage in that manner. Kansas produces about 3.0 million tons of silage annually, primarily from corn and sorghum. A majority of this silage is made and stored in either bunker, trench, or "drive-over" pile silos . Only 20 to 30% of these silos are sealed after filling. Producers who do not seal need to take a second look at the economics of this highly troublesome "technology" before they reject it as unnecessary and uneconomical. The loss from a 100 × 250 ft silo filled with corn silage can exceed $10,000.
Keywords: Beef; Silage; Top spoilage; Silo; Bunker silo; Trench silo; Pile silo